Critical Evaluation of the Association Between Elevated Mean Corpuscular Volume and Alcohol‐Related Traffic Accidents: A Retrospective Study on 6244 Car Crash Cases. (2nd May 2019) - Porpiglia, Nadia M.; Bortolotti, Federica; Dorizzi, Romolo M.; Micciolo, Rocco; Tagliaro, Franco
Abstract : Background: Erythrocyte mean corpuscular volume (MCV) has been used for decades as a biomarker of chronic alcohol abuse and in the treatment of alcohol dependence. More recently, it has also been adopted to investigate the fitness of subjects to hold the driving license to prevent traffic accidents. So far, however, the studies on the association of MCV with an increased risk of alcohol‐associated car accidents are extremely scarce, if not totally absent. To the best of our knowledge, the present work is the first specifically aimed at studying a plausible association between elevated MCV and crash accidents correlated with alcohol abuse. Methods: A total of 6, 244 drivers involved in traffic accidents underwent mandatory laboratory analyses including blood alcohol concentration (BAC) determination and MCV analysis. BAC and MCV determinations were performed by headspace gas chromatography and complete blood count, respectively. Results: The chi‐square test evaluating the proportions of subjects with elevated MCVs (>95 fl) yielded a highly significant result (χ 2 = 68.0; p < 0.001) in the blood samples where the BAC was above the legal limit (i.e., >0.5 g/l). However, when considering only drivers showing BACs in the range of 0.51 to 1.5 g/l, the frequencies of elevated MCV values are fairly comparable (χ 2 = 0.062, p = 0.80). In contrast, limiting the evaluation to BACs > 1.5 g/l, the frequency of elevated MCVs raised to 19.1% (χ 2 = 58.9, p value < 0.001 vs. the group with BAC within the legal limits). Conclusions: The present observations show that MCV increases are typically associated with drivers involved in accidents only if driving under severe alcohol intoxication, leading to a preliminary conclusion that, in the context of the certification of the fitness to the driving license, MCV fails to reveal individuals at risk who tend to drive in a condition of low‐to‐moderate alcohol intoxication.